Mobilities of Return Pacific Perspectives - Taylor, John; Lee, Helen (Pacific Series, 2017)
In recent decades, the term 'mobility' has emerged as a defining paradigm within the humanities. For scholars engaged in the multidisciplinary topics and perspectives now often embraced by the term Pacific Studies, it has been a much more longstanding and persistent concern. Even so, specific questions regarding 'mobilities of return'-that is, the movement of people 'back' to places that are designated, however ambiguously or ambivalently, as 'home'-have tended to take a back seat within more recent discussions of mobility, transnationalism and migration. This volume situates return mobility as a starting point for understanding the broader context and experience of human mobility, community and identity in the Pacific region and beyond. Through diverse case studies spanning the Pacific region, it demonstrates the extent to which the prospect and practice of returning home, or of navigating returns between multiple homes, is a central rather than peripheral component of contemporary Pacific Islander mobilities and identities everywhere.